Acquisition versus greenfield: The impact of the mode of foreign bank entry on information and bank lending rates - Sophie Claeys; Christa Hainz (Sveriges Riksbank, 2007)
Policy makers often decide to liberalize foreign bank entry but put limitations on the mode of entry. We study how different entry modes affect the lending rate set by foreign and domestic banks. Our model captures two essential features of banking competition in emerging markets: Domestic banks possess private information about their incumbent clients and foreign banks have better screening skills. Our model predicts that competition is stronger if foreign entry occurs through a greenfield investment and domestic banks' interest rates are thus lower. We find empirical support for this differential competition effect for a sample of banks from ten Eastern European countries for the period 1995-2003.
Keywords: G21; D4; L31; 330; Banking; Foreign Entry; Mode of Entry; Interest Rate; Asymmetric Information; Finanzmarktregulierung; Internationale Bank; Markteintritt; Bankenregulierung; Zins; Theorie; EU-Staaten (Osteuropa)